Petunjuk Al-Qur’an Bagi Keharusan Menggunakan Akal Pikiran Sebagai Sarana Berfilsafat - Ahmad Zikri Dwiatmaja; Indo Santalia; Syamsuddin Syamsuddin (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2024)
The Al-Qur'an, as the holy book inherited from the Prophet, is the basis for the formation of laws and legal systems in society that implements Islamic law, a support and guidance for humanity in shaping their lives. Meanwhile, philosophy is an attempt to understand and explore existential aspects, knowledge, ethics, logic, as well as concepts about the universe, life and reality in more depth. The research method used is a library study with a qualitative approach, the investigation is carried out through data collection in the form of journals and books or other literature as reference sources. The purpose of writing is to know the Qur'an as a basis for using the mind as a means of philosophizing. The results of this research are based on the Koran, intellectual intelligence is the greatest gift from Allah SWT. something given to humanity on earth. So that they can use their intelligence to be able to differentiate between good and bad and behave in a dignified and useful manner. Instructions in the Al-Qur'an as a basis for using reason mentioned in the Al-Qur'an to understand the truth of Allah's verses such as the universe, humans, civilization. This truth is a sign of the existence of the Almighty over everything, namely Allah SWT. So it is intelligence that is most likely to give birth to a religious and spiritual type of person. In the typology, intelligence seems to be an important goal of the Qur'an that must be developed at all levels of human life.